PENGARUH PEMBERIAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA KOPERASI BERKAH MANDIRI SEJAHTERA DI TANJUNG SARI BOGOR - Anwar, Faisal; Irawan, Ade; Riyanto, Sugeng (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to determine the effect of compensation on employee job satisfaction at Berkah Mandiri Sejahtera Cooperative in Tanjungsari. This research is important based on the low level of employee job satisfaction, which impacts their performance and productivity, as indicated by the data on salary reductions and increased employee turnover over the past three years. This study uses a quantitative method with an associative design to explore the relationship between the independent variable (compensation) and the dependent variable (job satisfaction). Data were collected through questionnaires distributed to all cooperative employees, with 35 respondents. The results showed that compensation had a significant effect on employee job satisfaction. The statistical test results indicated a coefficient of determination (R-Square) value of 77.6%, meaning that the compensation variable explains 77.6% of the variation in employee job satisfaction. The t-test showed a significance value of 0.000, less than 0.05, thus rejecting H0 and accepting Ha, indicating a significant effect between compensation and job satisfaction. The contribution of this research lies in strengthening empirical evidence that proper compensation, aligned with employees' needs, can enhance their job satisfaction, which in turn can improve company performance and productivity. This research is expected to serve as a reference for companies in formulating effective compensation policies to enhance employee satisfaction and performance.